Penentuan Bonus Karyawan Menggunakan Fuzzy Mamdani: (Studi Kasus PT. ABC) - Bella Khuri Aini Alfari; Tri Hastono; Wirinda Nur Aziza (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
Determining the provision of bonuses or rewards to employees plays a crucial role in maintaining the quality and motivation of employees. One effort that can be made to establish a bonus policy is by implementing the fuzzy Mamdani method as a systematic approach in determining employee bonuses, particularly at PT. ABC. By utilizing the fuzzy Mamdani method to process subjectivity in evaluations, it generates membership levels that allow for a more contextual employee assessment. Through the analysis of data involving various performance variables and bonus criteria, this research aims to present a fuzzy Mamdani system model that can support accurate and adaptive decision-making in determining employee bonuses. The results of this research and the evaluation of this model are expected to contribute significantly to the development of more effective bonus policies in the workplace of PT.